Clinical Neuroradiology: The ESNR Textbook - Barkhof, Frederik; Jäger, Rolf; Thurnher, Majda; Rovira, Àlex (Springer, 2020)
This superbly illustrated textbook, endorsed by the European Society of Neuroradiology, explains in detail the clinical importance of neuroradiology in complementing history taking and physical examination during the workup of patients suspected of having neurological, neurosurgical, or psychiatric disorders. The role of imaging of the brain and spinal cord is described across the full range of relevant conditions, including, for example, cerebrovascular diseases, trauma, CSF disorders, developmental malformations, autoimmune diseases, epilepsy, tumors and tumor-like conditions, neurodegenerative diseases, metabolic conditions, and bipolar and depressive disorders. The structured approach to imaging and image analysis will ensure that the book is an invaluable resource for neuroradiologists in training and clinicians alike. Starting from the clinical indication, suggestions for imaging protocols are provided and checklists of common findings and aspects key to interpretation are presented. The book is published within the SpringerReference program, which combines thorough coverage with access to living editions constantly updated via a dynamic peer-review process